The Influence Of Electronic Word Of Mouth And Brand Image On Purchasing Decisions At Shopee - SAMSUDDIN, Ardian (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:With the fourth industrial revolution, technology around the world is developing faster, enabling faster information transfer (Nabilah et al., 2021). This is exacerbated by the increasing number of internet users around the world. Internet use is prevalent in many areas of everyday life. The economic sector is the only industry that has been negatively affected by the emergence of the internet (Malay, 2022).Methodology: The methodology used in this research is quantitative. Consumers who took part in this survey had previously made purchases at Shopee.com. On the other hand, the minimum number of samples needed for this research is around 90 samples by using a questionnaire in determining the research. While the analysis tool uses multiple regression via SPSS.Findings: The results of the study suggest that keeping this in mind, it can be said that Electronic Word Of Mouth is a useful word of mouth tool for Shopee purchase recommendations. Electronic Word Of Mouth has a more dominant influence on the purity of purchases at Matahari Depart Store, so it is suggested that Matahari's management must be able to provide good service to consumers.Implication: The implications of the research state that brand image lifestyle and electronic word of mouth promotion on purchasing decisions are very decisive for marketing. So that the brand can create a good product and increase purchases.